Performance Enhancing Effect of Metabolic Pre-conditioning on Upper-Body Strength-Endurance Exercise - Birnbaumer, Philipp; Müller, Alexander; Tschakert, Gerhard; Sattler, Matteo C.; Hofmann, Peter (Frontiers in Physiology, 2018)
High systemic blood lactate (La) was shown to inhibit glycolysis and to increase oxidative metabolism in subsequent anaerobic exercise. Aim of this study was to examine the effect of a metabolic pre-conditioning (MPC) on net La increase and performance in subsequent pull-up exercise (PU). Nine trained students (age: 25.1±1.9 yrs; BMI: 21.7±1.4) performed PU on a horizontal bar with legs placed on a box (angular hanging) either without or with MPC in a randomized order. MPC was a 26.6±2 s all out shuttle run. Each trial started with a 15-min warm-up phase. Time between MPC and PU was 8 min. Heart rate (HR) and gas exchange measures (VO2, VCO2, VE) were monitored, La and glucose were measured at specific time points. Gas exchange measures were compared by area under the curve (AUC). In PU without MPC, La increased from 1.24±0.4 to 6.4±1.4 mmol·l-1, whereas with MPC, PU started at 9.28±1.98 mmol·l-1 La which increased to10.89±2.13 mmol·l-1. With MPC, net La accumulation was significantly reduced by 75.5% but performance was significantly increased by 1 rep (4%). Likewise, net oxygen uptake VO2 (50% AUC), pulmonary ventilation VE (34% AUC) and carbon dioxide VCO2 production (26% AUC) were significantly increased during PU but respiratory exchange ratio (RER) was significantly blunted during work and recovery. MPC inhibited glycolysis and increased oxidative metabolism and performance in subsequent anaerobic upper-body strength-endurance exercise.